2021
DOI: 10.3389/fneur.2021.562090
|View full text |Cite
|
Sign up to set email alerts
|

White Matter Injury After Intracerebral Hemorrhage

Abstract: Spontaneous intracerebral hemorrhage (ICH) accounts for 15% of all stroke cases. ICH is a devastating form of stroke associated with high morbidity, mortality, and disability. Preclinical studies have explored the mechanisms of neuronal death and gray matter damage after ICH. However, few studies have examined the development of white matter injury (WMI) following ICH. Research on WMI indicates that its pathophysiological presentation involves axonal damage, demyelination, and mature oligodendrocyte loss. Howe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(28 citation statements)
references
References 121 publications
0
28
0
Order By: Relevance
“…Perihematomal edema (PHE), associated with a worse prognosis, has been recognized as an evident marker of SBI after ICH and a likely therapeutic pathophysiological target for attenuating SBI ( Brouwers and Greenberg, 2013 ; Bautista et al, 2021 ; Chen et al, 2021 ). Furthermore, it was displayed that intracranial hematoma expands to further and adjacent brain tissues through perivascular spaces, white matter tracts, and their perineurium ( Yin et al, 2013 ; Fu et al, 2021 ), particularly if ICH is combined with an intraventricular hemorrhage ( Bosche et al, 2020 ). All these pathological changes in the hematoma site make the nerve fibers distended and distorted and finally disrupted to a point at which they cannot be rescued.…”
Section: Pathological Changes After Intracerebral Hemorrhagementioning
confidence: 99%
“…Perihematomal edema (PHE), associated with a worse prognosis, has been recognized as an evident marker of SBI after ICH and a likely therapeutic pathophysiological target for attenuating SBI ( Brouwers and Greenberg, 2013 ; Bautista et al, 2021 ; Chen et al, 2021 ). Furthermore, it was displayed that intracranial hematoma expands to further and adjacent brain tissues through perivascular spaces, white matter tracts, and their perineurium ( Yin et al, 2013 ; Fu et al, 2021 ), particularly if ICH is combined with an intraventricular hemorrhage ( Bosche et al, 2020 ). All these pathological changes in the hematoma site make the nerve fibers distended and distorted and finally disrupted to a point at which they cannot be rescued.…”
Section: Pathological Changes After Intracerebral Hemorrhagementioning
confidence: 99%
“…This cell type is known to play an important role in maintaining myelin integrity and regulating axon growth in the spinal cord [39,40]. After SCI, they undergo both necrosis and apoptosis acutely, which causes demyelination and impairs axon function and survival [41]. Therefore, the protection of oligodendrocytes and consequently myelin production has beneficial effects on the functional outcomes post SCI [42].…”
Section: Discussionmentioning
confidence: 99%
“…Evidence indicates that ICH induces WM injury via multiple mechanisms including mechanical injury, oxidative stress (in part haemoglobin-/iron-mediated), neuroinflammation, excitotoxicity, and blood-brain barrier (BBB) disruption. 30 Changes in the axonal cytoskeleton after ICH not only impact the physical structure of the axon but also mitochondrial transport and function leading to degeneration. 31 Recent studies have suggested that the inhibition of histone deacetylases (HDACs) with scriptaid or conditional knockout of HDAC2 in microglia can reduce ICH-induced neuroinflammation and WM injury in mice.…”
Section: Haematomamentioning
confidence: 99%
“…AVM, arteriovenous malformations; BBB, blood-brain barrier; CAA, cerebral amyloid angiopathy; CCM, cerebral cavernous malformation; COL4A1, α1 chain of collagen type IV; ICH, intracerebral haemorrhage; L-NAME, N ω -nitro-L-arginine methyl ester. (A) Rodent models Model Aetiological or pathophysiological mechanisms addressed, translational value Autologous blood injection Endogenous haematoma clearance 26 , 28 , 29 , 53 White matter injury and axonal degeneration 30 , 100 Cell death 29 , 51 , 101 , 102 Perihaematomal oedema 49 , 51 , 53 , 101 , 102 BBB impairment 22 , 45 , 47 , 49 Inflammation 28 , 49 , 51 , 52 , 53 , 101 , 102 , 103 Immunosuppression 58 Cardiac complications 63 , 64 Can be combined with comorbidities: angiotensin II infusion + hyperglycaemia (incl. haematoma expansion), 22 hyperglycaemia 102 Collagenase injection Anticoagulation 12 , 13 Endogenous haematoma clearance 26 , …”
Section: Limitations Of Animal Modelsmentioning
confidence: 99%